SPRITUALITAS MANUSIA DAN MA’RIFAT - Mat Jalil (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Ma’rifat searching of The God’s unsure on a seeker, makes a special vibration waves about God’s things, and after those are founded, that person will confess as God’s servant. In the second valley, if the things which have been searched before are founded, even it’s slightly explicit (melik-melik), that person will taste the love which make everything implicit (melik) before becomes clear (melek) and even follow it (melok). The love will deliver him to the next valley of ma’rifat; holly valley. The next ecstacy is kneeling down and full of grateful, then feeling beyond amazed by the intended face, fana fi-ilallah.